On certain families of sparse numerical semigroups with Frobenius number even - Tizziotti, G.; Villanueva, J. (Algebra and Discrete Mathematics, 2019)
This paper is about sparse numerical semigroups and applications in the Weierstrass semigroups theory. We describe and find the genus of certain families of sparse numerical semigroups with Frobenius number even and we also study the realization of the elements on these families as Weierstrass semigroups.